2021
DOI: 10.2147/cmar.s320490
|View full text |Cite
|
Sign up to set email alerts
|

βKlotho Inhibits Cell Proliferation by Downregulating ELK4 and Predicts Favorable Prognosis in Prostate Cancer

Abstract: Objective Prostate cancer (PCa) ranks as the second common malignancy in males worldwide. Although conspicuous progressions in diagnosis and treatment have been achieved in the past decades, the prognosis expectation of PCa remains unsatisfied yet. To improve the prognosis prediction of PCa, more specific biomarkers are needed. In this retrospective research, we focused on βKlotho and ETS-like transcription factor 4 (ELK4), aiming to identify potential prognostic biomarkers for PCa. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…S4 B ). While SP2, ELK4, and E2F are implicated in tumor growth and metastasis, CCAAT-binding transcription factors have been found to be good prognostic indicators in cancer ( 60 63 ). The genome browser tracks are shown in SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S4 B ). While SP2, ELK4, and E2F are implicated in tumor growth and metastasis, CCAAT-binding transcription factors have been found to be good prognostic indicators in cancer ( 60 63 ). The genome browser tracks are shown in SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that ELK4 expression is involved in the formation of a tumor. ELK4 acts as a prognostic marker, and it is highly expressed in various cancers, such as glioblastoma, 13 prostate cancer, 14 esophageal squamous cell carcinoma, 15 and breast cancer. 16 ELK4 promotes cell proliferation and its presence indicated a poor prognosis in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Changlin, et al also reported that β-Klotho downregulated the expression of ELK4, inducing apoptosis and inhibition of cell proliferation in prostate cancer cells. 14 Furthermore, a persistent HPV infection may accelerate the progression to CC. For instance, CaCxSLCs exhibited highly tumorigenic abilities through selectively overexpressing the HPV oncoprotein E6 in the CC stem cells.…”
Section: Discussionmentioning
confidence: 99%